Dibujo artístico y su incidencia en el desarrollo de las Artes plásticas del séptimo año de educación general básica paralelo B de la Unidad Educativa Rafael Vásconez Gómez período lectivo 2016-2017 - Izurieta Vélez, Mayra Katherine (2017)
The arts form a language that moves through different elements, such as movement, a gesture, word, image or light, among others, that allow us to express ourselves, and have as a particularity: creativity is always implicit, research made a diagnosis to determine the scarce use of the artistic drawing for the development of the plastic arts, the purpose was to encourage and apply this project to improve the creativity of students and develop basic skills according to the theme, field research within the educational and bibliographical establishment because its theoretical contextualization requires the criteria of various authors, a proposal was elaborated that consists of a training guide with their respective workshops. Its objective was to encourage the plastic arts as the artistic drawing through workshops, to develop skills, skills in the students of the seventh year of basic general education parallel "B" of the educational unit "Rafael Vásconez Gómez" teaching period 2016-2017 morning session, art is a good strategy for education in all areas. Therefore, this research process aims to promote creative, reflexive and critical thinking through artistic drawing learning tool that stimulates to create and innovate. And generate knowledge in the girls, the proposed proposal consists of a training guide consisting of various activities and techniques of painting, color differentiation, shading that help stimulate the practice of this activity and their results were considered an important contribution for its formation, generating awareness about the development of creativity in artistic activities, the impact strengthened the intelligence of the children on the subject, where the direct beneficiaries were the students of the morning section who will have a cognitive development according to their needs of academic training.